RANCANG BANGUN SISTEM INFORMASI WEBSITE PROGRAM STUDI TEKNIK INFORMATIKA UNUSIA MENGGUNAKAN METODE WATERFALL DAN FRAMEWORK LARAVEL: DESIGN AND BUILD OF INFORMATION SYSTEM WEBSITE INFORMATION ENGINEERING STUDY PROGRAM UNUSIA USING WATERFALL METHOD AND LARAVEL FRAMEWORK - Fernandy, Handy; Arifin A Abd Karim (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2022)
The development of the internet has been used for various purposes, one of which is in conveying information through the media website. website is the cheapest, effective and efficient promotional media if it can be managed properly. Department of Information Engineering, Faculty of Engineering and Computer Science, University of Nahdaltul Ulama Indonesia has a website as a medium for disseminating information to students, lecturers, staff, and the general public, but it is not optimally used and there are shortcomings such as the appearance of the website that is less attractive and not responsive. Therefore, it is necessary to design a website as a medium of information. This research uses the waterfall method. Making a website information system using the PHP Laravel programming language framework and Javascript with a database using Lite Speed ​​and other supporting software. The result of the research is that a website-based information system has been built that can facilitate students, lecturers, staff and the general public in obtaining information related to activities or activities in Information Engineering, Faculty of Engineering and Computer Science, Nahdlatul Ulama University, Indonesia. The website information system as a dynamic source of information will continue to display the latest or updated news related to majors or study programs